2005
DOI: 10.1248/bpb.28.1476
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2D6*10 on the Pharmacokinetics of R- and S-Carvedilol in Healthy Japanese Volunteers

Abstract: Carvedilol is a b-adrenoceptor antagonist, and has been clinically used to treat chronic heart failure as well as hypertension, angina pectoris, and cardiac arrhythmias. [1][2][3][4] Carvedilol is highly lipophilic and eliminated predominantly by hepatic metabolism, with renal excretion accounting for only 0.3% of the administered dose.5) The drug is absorbed rapidly from the gastrointestinal tract after oral administration; however, the amount of unchanged drug excreted in the feces was 23% of the administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
39
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 22 publications
2
39
0
3
Order By: Relevance
“…[13][14][15] Assay of Carvedilol Enantiomers The amount of carvedilol in the samples was measured using chiral high performance liquid chromatography (HPLC) as described by Saito et al with minor modifications. [7][8][9][10]16) Briefly, carvedilol was extracted from the samples (0.1 ml) with 5 ml diethylether after alkalization in 3 ml of 0.1 M Britton-Robinson buffer (pH 8.5). The organic phase was transferred and evaporated dry in a water bath at 45°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Assay of Carvedilol Enantiomers The amount of carvedilol in the samples was measured using chiral high performance liquid chromatography (HPLC) as described by Saito et al with minor modifications. [7][8][9][10]16) Briefly, carvedilol was extracted from the samples (0.1 ml) with 5 ml diethylether after alkalization in 3 ml of 0.1 M Britton-Robinson buffer (pH 8.5). The organic phase was transferred and evaporated dry in a water bath at 45°C.…”
Section: Methodsmentioning
confidence: 99%
“…6) In addition, our previous findings indicated that R-carvedilol is metabolized mainly by CYP2D6 and partly by CYP1A2, 2C9, and 3A4, and that S-carvedilol is metabolized mainly by CYP1A2 and partly by CYP2C9, 2D6, and 3A4. [7][8][9][10] On the other hand, Ohno et al found that uridine 5Ј-diphosphate (UDP)-glucuronosyltransferase (UGT) 2B7, 2B4, and 1A1 are capable of catalyzing the glucuronidation of carvedilol using microsomes from insect cells expressing human UGT. 11) In addition, they have demonstrated that glucuronidation of R-carvedilol is mediated by UGT1A1 and 2B4, and that glucuronidation of S-carvedilol is mediated by UGT2B7 and 2B4.…”
mentioning
confidence: 99%
“…The cells were seeded at a density 5ϫ10 5 The treatment of Caco-2 cells with b-NF or VD 3 (an inducer of CYP3A4) was performed as described previously. Reverse transcription of extracted total RNA was performed using an Omniscript ® RT Kit (QIAGEN) and random hexamer (QIAGEN) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5] Carvedilol is metabolized extensively via aliphatic side-chain oxidation, aromatic ring oxidation, and conjugation pathways.6) Oldham and Clarke reported that oxidative activity of carvedilol is observed in cytochrome P450 (CYP) 2D6, 1A2, 3A4, and 2C9.7) In addition, Ohno et al reported that UDPglucuronosyltransferase (UGT) 2B7, 1A1, and 2B4 are capable of catalyzing the glucuronidation of carvedilol.8) However, it has been unknown whether the intestine also plays a role in the first-pass presystemic metabolism of carvedilol, although several CYP and UGT isoforms are expressed in human intestinal epithelial cells. 9,10) We previously investigated the metabolism of carvedilol in human intestinal epithelial Caco-2 cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation